2018
DOI: 10.1155/2018/5135203
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Anxiety in Greek Children and Their Parents When Presenting for Routine Surgery

Abstract: Background A surgical operation in pediatric patients is a rather stressful experience for both children and their parents. The aim of this study was to assess the effect of specific demographic characteristics in parent's and children's preoperative anxiety. Methods The sample was composed of 128 Greek-speaking children (1–14 years of age) who had to undergo minor surgery in a University General Hospital. Before surgical operation, the Spielberger State-Trait Anxiety Inventory (STAI) questionnaire and a quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 30 publications
6
40
2
Order By: Relevance
“…It has been reported higher in several studies; which ranges 50-75% patients in studies done from USA and Brazil 8,9 but studies done in Greek and Brazil reported relatively smaller (42% and 39%). 10,11 Younger age children, female gender, past bad hospital experience, past anesthetic, and surgical exposure, intravenous mode of anesthetic induction, increased number of people during induction, and low socioeconomic status of the parent are known to experience preoperative anxiety more frequently. [11][12][13] Children are influenced by parental advice and guidance in coping with new or stressful situations; on the other hand, parents may be anxious varying with the information given regarding anesthesia and associated risks, which may result in fear and anxiety for their children.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported higher in several studies; which ranges 50-75% patients in studies done from USA and Brazil 8,9 but studies done in Greek and Brazil reported relatively smaller (42% and 39%). 10,11 Younger age children, female gender, past bad hospital experience, past anesthetic, and surgical exposure, intravenous mode of anesthetic induction, increased number of people during induction, and low socioeconomic status of the parent are known to experience preoperative anxiety more frequently. [11][12][13] Children are influenced by parental advice and guidance in coping with new or stressful situations; on the other hand, parents may be anxious varying with the information given regarding anesthesia and associated risks, which may result in fear and anxiety for their children.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Younger age children, female gender, past bad hospital experience, past anesthetic, and surgical exposure, intravenous mode of anesthetic induction, increased number of people during induction, and low socioeconomic status of the parent are known to experience preoperative anxiety more frequently. [11][12][13] Children are influenced by parental advice and guidance in coping with new or stressful situations; on the other hand, parents may be anxious varying with the information given regarding anesthesia and associated risks, which may result in fear and anxiety for their children. Well-prepared parents, in turn, will be able to support their children and help themselves and their children suitably for an upcoming surgery.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A more recent study by Charana et al (2018) examined the effect of specific demographic characteristics in parents' and childrens' preoperative anxiety. The study consisted of 128 Greek speaking children ranging 1-14 years of age.…”
Section: Pre-operative Anxietymentioning
confidence: 99%